Lithium cobalt oxide composite positive electrode material with coating layer, preparation method of lithium cobalt oxide composite positive electrode material, positive electrode and battery
By using lithium cobalt oxide and its metal oxide cladding of T2 and O2 phases in LiCoO2 positive electrode material, the stability problem of the material at high voltage is solved, and better electrochemical performance and cycle life are achieved.
Patent Information
- Application Number
- CN202411773983.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing LiCoO2 positive electrode materials have stability problems at high voltages, resulting in interface side reactions and structural damage, affecting their electrochemical properties.
A lithium cobalt oxide composite cathode material with a clad layer is composed of lithium cobalt oxide in T2 and O2 phases, and a metal oxide clad layer is formed by coating solid phase sintering and molten salt ion exchange methods.
It improves the stability and electrochemical performance of lithium cobalt oxide materials at high voltages, inhibits interfacial side reactions, and extends the cycle life.
Smart Images

Figure CN119601631A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium cobalt oxide composite positive electrode material with a coating layer, a preparation method thereof, a positive electrode and a battery. Background Art
[0002] LiCoO2, a lithium-containing layered transition metal oxide cathode material, was first reported by John B. Goodenough et al. in 1980. The layered structure of LiCoO2 is Li + It provides a 2D diffusion channel and has the advantages of large specific capacity, high voltage, and good cycle performance, and has been widely studied and applied. The space group of conventional LiCoO2 is R-3m, Li + and Co 3+ Layers are arranged alternately in a cubic close-packed O 2- In the octahedral positions formed, LiO6 and CoO6 octahedra are stacked with shared edges, and the arrangement order of the O layer is ABCABC, which belongs to the O3 phase.
[0003] The theoretical capacity of O3 phase LiCoO2 is as high as 274mAh / g, which has a very high volumetric energy density, but the actual capacity release of LiCoO2 is closely related to the charging voltage. To further improve the capacity performance and energy density of LiCoO2, it is necessary to continuously increase the charging voltage of LiCoO2. Therefore, researchers have conducted extensive research on high-voltage LiCoO2. With various theoretical studies, coating and doping modifications, the voltage of LiCoO2 has been gradually increased, but when charged to 4.5V and above, the capacity attenuation mechanism of LiCoO2 in organic electrolyte is more complicated, which is not only related to the crystal structure and electronic structure of the material itself, but also to the type of electrolyte and the properties of the interface. At the O3-H1-3-O1 phase transition that begins at 4.5V, the reversibility of the slip phase transition of the CoO2 plate layer is reduced, and the particles undergo a c-axis contraction of more than 3%. At the same time, due to the Co3 + / 4 + :3d energy band and O 2- : The top of the 2p band overlaps, resulting in the O 2- It will provide charge compensation and cause oxidation reaction, and O2 will be released from the lattice, causing damage to the material. In addition, some researchers have found that when charged to a higher potential, the interface of LiCoO2 is unstable and a spinel phase with low electrochemical activity will be generated. In addition, some researchers believe that certain solvents in the organic electrolyte will react with the surface of LiCoO2, causing the LiCoO2 interface to change or even dissolve.
[0004] Therefore, developing LiCoO2 cathode materials that are more stable and have higher energy density at high voltages is the current mainstream research direction. T2 phase lithium cobalt oxide has obvious advantages over traditional O3 phase lithium cobalt oxide in terms of capacity, rate and cyclability. O2 phase LiCoO2 has a different spatial arrangement from O3 phase LiCoO2, and can still maintain a stable crystal structure at a higher delithiation state. The CoO6 octahedron in the O2 phase LiCoO2 has a stronger Co-O bond, which enhances the structural stability to resist proton attack and prolongs the cycle life in aqueous electrolytes. In addition, the O2 phase LiCoO2 undergoes a reversible phase change during the cycle process and will not be converted into the thermodynamically stable O3 phase LiCoO2 or spinel phase. Combined with the above advantages, O2 phase LiCoO2 can be used as another solution for LiCoO2 cathode materials at high voltages. However, O2 phase LiCoO2 also has disadvantages, such as low phase transition temperature. It will transform to O3 phase above 230°C and will completely transform to O3 phase above 280°C. The conventional O3 phase LiCoO2 in industry now requires the substrate and coating material to be mixed and then subjected to secondary high-temperature calcination to achieve coating. Therefore, the coating technology used for conventional O3 phase LiCoO2 is difficult to achieve effective coating of O2 phase LiCoO2, and the interfacial side reactions between the positive electrode material and the electrolyte cannot be effectively suppressed.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a lithium cobalt oxide composite positive electrode material with a coating layer, a preparation method thereof, a positive electrode and a battery.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a lithium cobalt oxide composite positive electrode material with a coating layer, comprising:
[0009] The main body and the coating layer coated outside the main body, the chemical formula of the main body is Li x Na y Co 1-z M z O2, wherein 0.7≤x≤0.74, 0<y≤0.1, 0≤z≤0.1, and M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn and Nb;
[0010] The coating layer is a metal oxide, and the thickness of the coating layer is less than or equal to 1 μm;
[0011] The crystalline phase in the main body is a composite phase of T2 and O2.
[0012] In an optional embodiment, at least one of the following technical features (1) to (5) is included:
[0013] (1) The thickness of the coating layer is 0.05 to 1 μm;
[0014] (2) The particle size of the lithium cobalt oxide composite positive electrode material with the coating layer is 1 to 20 μm;
[0015] (3) The main peak of the XRD spectrum of the lithium cobalt oxide composite positive electrode material with a coating layer is located at 17.80±0.15°, and there is an O2 phase characteristic peak at 18.40±0.15°;
[0016] (4) the metal oxide is at least one selected from the group consisting of aluminum oxide, magnesium oxide, yttrium oxide, niobium oxide, lanthanum oxide and zirconium oxide;
[0017] (5) The amount of O2 phase material in the T2 and O2 composite phase is greater than 0 and less than or equal to 10%.
[0018] In a second aspect, the present invention provides a method for preparing a lithium cobalt oxide composite positive electrode material with a coating layer as in the aforementioned embodiment, comprising:
[0019] The sodium cobaltate P2 phase precursor is mixed with a coating material and then subjected to coating solid phase sintering, wherein the coating material is the metal oxide and the sintering temperature is 550-750° C., to obtain a P2 phase precursor with a coating layer;
[0020] The P2 phase precursor with the coating layer is mixed with a lithium source and then subjected to molten salt ion exchange, so that the lithium element is exchanged with the sodium element in the P2 phase precursor with the coating layer, so that the P2 phase is transformed into a T2 and O2 composite phase.
[0021] In an optional embodiment, before performing the coating solid phase sintering, the process further includes obtaining the sodium cobaltate P2 phase precursor:
[0022] The first mixed material is subjected to synthetic solid phase sintering, wherein the first mixed material includes sodium element and cobalt element, wherein the molar ratio of the sodium element to the cobalt element is 0.6-1.0:1, to obtain a sodium cobaltate P2 phase precursor.
[0023] In an optional embodiment, the first mixture further includes an M element, and M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn and Nb.
[0024] In an optional embodiment, the cobalt element in the first mixed material is provided by a cobalt source, and the cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide;
[0025] Optionally, the M element is doped into the cobalt source.
[0026] In an optional embodiment, the sodium element in the first mixture is provided by a sodium source, and the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
[0027] In an optional embodiment, the sintering conditions of the synthetic solid phase sintering are: heating to 700-900° C. at a rate of 1-10° C. / min and keeping the temperature for 8-30 hours.
[0028] In an optional embodiment, at least one of the following technical features (1) to (4) is included;
[0029] (1) The sintering conditions of the coated solid phase sintering are: heating to 550-750°C at 1-10°C / min and keeping warm for 3-12h;
[0030] (2) The conditions for molten salt ion exchange are: heating to 180-300°C at 1-10°C / min and keeping warm for 0.5-12h;
[0031] (3) The lithium source is composed of at least two of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide, which can be eutectic in the range of 180 to 300° C.;
[0032] (4) The molar ratio of the lithium element in the lithium source to the sodium element in the P2 phase precursor with the coating layer is 1 to 20:1.
[0033] In an optional embodiment, a crude positive electrode material is obtained after molten salt ion exchange, and after obtaining the crude positive electrode material, it also includes washing and drying to obtain a lithium cobalt oxide composite positive electrode material with a coating layer on the surface;
[0034] Optionally, the drying temperature is 80-150° C., and the drying time is ≥12 h.
[0035] In a third aspect, the present invention provides a positive electrode, the active component of which includes a lithium cobalt oxide composite positive electrode material with a coating layer as described in the aforementioned embodiment, or a positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.
[0036] In a fourth aspect, the present invention provides a battery, comprising the positive electrode according to the aforementioned embodiment.
[0037] The present invention has the following beneficial effects:
[0038] The lithium cobalt oxide composite positive electrode material with coating provided by the present invention mainly comprises lithium cobalt oxide of T2 phase and O2 phase. The lithium cobalt oxide of T2 phase has better capacity, rate and cyclability than that of O3 phase. The lithium cobalt oxide of O2 phase can still maintain the stability of crystal structure in a higher delithiation state than that of O3 phase. The lithium cobalt oxide of O2 phase undergoes reversible phase change during the cycle process and will not be converted into the thermodynamically stable lithium cobalt oxide of O3 phase or spinel phase. The metal oxide coating layer coated on the surface of the main body can suppress the interfacial side reaction problem of lithium cobalt oxide at high voltage, thereby further improving the electrochemical performance of the lithium cobalt oxide material. Therefore, the lithium cobalt oxide composite positive electrode material with coating provided by the present invention has better electrochemical performance.
[0039] The preparation method provided by the present invention can achieve coating of T2 and O2 composite phase lithium cobalt oxide material by coating the P2 phase precursor and then performing molten salt ion exchange, thereby obtaining a composite positive electrode material having a surface coating layer and a main body of T2 and O2 composite phase lithium cobalt oxide. Compared with high-speed fusion coating or low-temperature sintering coating of the finished O2 phase lithium cobalt oxide material, this coating method has significantly higher bonding properties because the coating layer is formed at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0041] Figure 1 The XRD diagram of the T2 and O2 composite phase lithium cobalt oxide material with coating layer prepared in Example 1;
[0042] Figure 2 This is the XRD pattern of the lithium cobalt oxide material prepared in Comparative Example 3;
[0043] Figure 3 CP-EPMA image of the P2 phase precursor during the preparation process of Example 1;
[0044] Figure 4 This is the CP-EPMA image of the T2 and O2 composite phase lithium cobalt oxide material with a coating layer prepared in Example 1. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0046] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0047] The lithium cobalt oxide composite positive electrode material with a coating layer provided in an embodiment of the present invention comprises:
[0048] The main body and the coating layer coated outside the main body, the chemical formula of the main body is Li x Na y Co 1-z M z O2, wherein 0.7≤x≤0.74, 0<y≤0.1, 0≤z≤0.1, and M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn and Nb;
[0049] The coating layer is a metal oxide, and the thickness of the coating layer is less than or equal to 1 μm;
[0050] The crystalline phase in the main body is a composite phase of T2 and O2.
[0051] The lithium cobalt oxide composite positive electrode material with coating provided by the present invention mainly comprises lithium cobalt oxide of T2 phase and O2 phase. The lithium cobalt oxide of T2 phase has better capacity, rate and cyclability than that of O3 phase. The lithium cobalt oxide of O2 phase can still maintain the stability of crystal structure in a higher delithiation state than that of O3 phase. The lithium cobalt oxide of O2 phase undergoes reversible phase change during the cycle process and will not be converted into the thermodynamically stable lithium cobalt oxide of O3 phase or spinel phase. The metal oxide coating layer coated on the surface of the main body can suppress the interfacial side reaction problem of lithium cobalt oxide at high voltage, thereby further improving the electrochemical performance of the lithium cobalt oxide material. Therefore, the lithium cobalt oxide composite positive electrode material with coating provided by the present invention has better electrochemical performance.
[0052] Furthermore, the main peak of the XRD spectrum of the lithium cobalt oxide composite positive electrode material with a coating layer is located at 17.80±0.15°, and there is an O2 phase characteristic peak at 18.40±0.15°.
[0053] Optionally, the amount of O2 phase material in the T2 and O2 composite phase is greater than 0 and less than or equal to 10% (for example, 0.1%, 0.5%, 1%, 2%, 5% or 10%).
[0054] Optionally, to further improve the electrochemical performance of the composite lithium cobalt oxide, the thickness of the coating layer is 0.05 to 1 μm (eg, 0.05 μm, 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm or 1 μm).
[0055] Optionally, to further improve the electrochemical performance of the composite lithium cobalt oxide, the particle size of the lithium cobalt oxide composite positive electrode material with a coating layer is 1 to 20 μm. The particle size here refers to the particle size of a single particle of the lithium cobalt oxide composite positive electrode material with a coating layer.
[0056] Optionally, the metal oxide is selected from at least one of aluminum oxide, magnesium oxide, yttrium oxide, niobium oxide, lanthanum oxide and zirconium oxide. Different types of metal oxide coatings impart slightly different properties to the positive electrode material, but the above-mentioned metal oxides all have positive effects on improving the capacity, energy density and cycle life of the positive electrode material.
[0057] Optionally, in order to further improve the electrochemical performance of the composite lithium cobalt oxide, the ratio of lithium element to cobalt element in the lithium cobalt oxide composite positive electrode material with a coating layer is 0.70 to 0.74:1 (eg, 0.7:1, 0.72:1 or 0.74:1).
[0058] The method for preparing the lithium cobalt oxide composite positive electrode material with a coating layer provided in an embodiment of the present invention comprises:
[0059] The sodium cobaltate P2 phase precursor is mixed with a coating material and then subjected to coating solid phase sintering, wherein the coating material is a metal oxide and the sintering temperature is 550 to 750° C. (e.g., 550° C., 600° C., 650° C., 700° C. or 750° C.) to obtain a P2 phase precursor with a coating layer;
[0060] The P2 phase precursor with the coating layer is mixed with a lithium source and then subjected to molten salt ion exchange, so that the lithium element is exchanged with the sodium element in the P2 phase precursor with the coating layer, and the P2 phase is transformed into a T2 and O2 composite phase.
[0061] The preparation method of the lithium cobalt oxide composite positive electrode material with a coating layer provided by the present invention is to coat the surface of the P2 phase precursor with a metal oxide and then perform molten salt ion exchange with a lithium source to convert the P2 phase sodium cobalt oxide inside the coating layer into the O2 phase lithium cobalt oxide, thereby obtaining a lithium cobalt oxide composite material with a metal oxide coating layer on the surface and a crystal phase structure of a T2 and O2 composite phase. The material can suppress the interface side reaction problem of lithium cobalt oxide at high voltage. At the same time, because the T2 phase and O2 phase lithium cobalt oxide body have better structural stability, it can achieve a higher capacity and better cycle stability than conventional commercial O3 phase lithium cobalt oxide at high voltage. This method overcomes the problem that the O2 phase lithium cobalt oxide has a low phase transition temperature and cannot be directly coated on the surface, and it is difficult to form a metal oxide coating layer on the surface of the O2 phase lithium cobalt oxide.
[0062] The preparation method specifically comprises:
[0063] S1. Synthesis solid phase sintering
[0064] Mixing various raw materials uniformly to obtain a first mixed material, wherein the first mixed material includes sodium element and cobalt element, wherein the molar ratio of the sodium element to the cobalt element is 0.6 to 1.0:1 (e.g., 0.6:1, 0.8:1 or 1:1);
[0065] The first mixed material is heated to 700-900°C (e.g. 700°C, 800°C or 900°C) at 1-10°C / min (e.g. 1°C / min, 5°C / min or 1°C / min), kept warm for 8-30h (e.g. 8h, 10h, 20h or 30h), and then cooled in the furnace to obtain a P2 phase precursor. The P2 phase precursor is ground and sieved to obtain a powder with a particle size of 5-20 μm for later use.
[0066] Optionally, the raw materials mixed to obtain the first mixed material include a cobalt source, and the cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide;
[0067] Optionally, the first mixture also includes an M element, and M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn and Nb.
[0068] Optionally, the M element is doped in the cobalt source, or the M element is a metal oxide, metal hydroxide or a single substance that is mixed alone.
[0069] Optionally, the raw materials mixed to obtain the first mixed material include a sodium source, and the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
[0070] S2, coating solid phase sintering
[0071] The powdered P2 phase precursor obtained in the previous step is mixed evenly with a coating material, wherein the coating material is a metal oxide used to form a coating layer;
[0072] After mixing evenly, heat the mixture to 550-750°C (e.g., 550°C, 600°C, 650°C, 700°C or 750°C) at a rate of 1-10°C / min (e.g., 1°C / min, 5°C / min or 1°C / min), keep it at this temperature for 3-12h (e.g., 3h, 5h, 8h, 10h or 12h), and then cool it in the furnace to obtain a P2 phase precursor with a coating layer.
[0073] S3, molten salt ion exchange
[0074] The P2 phase precursor of the coating layer is mixed evenly with the lithium source. After mixing evenly, the temperature is raised to 180-300°C (for example, 180°C, 200°C, 250°C or 300°C) at a rate of 1-10°C / min (for example, 1°C / min, 5°C / min or 1°C / min), and the mixture is kept warm for 0.5-12h (for example, 0.5h, 1h, 3h, 5h, 8h, 10h or 12h) to perform molten salt ion exchange. After cooling with the furnace, a metal oxide coating layer is obtained on the surface. Since lithium ions are not completely evenly distributed during the molten salt ion exchange process, lithium distribution in some crystal phases is relatively small, and in some crystal phases is relatively large, the crystal phase of the obtained lithium cobalt oxide positive electrode material is a composite crystal phase of T2 phase and O2 phase.
[0075] Optionally, the lithium source consists of at least two of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide, which can be eutectic in the range of 180-300°C.
[0076] Generally, a single lithium source has a high melting point and it is difficult to ensure that it can melt within 180-300°C. At least two lithium sources need to be mixed in a specific ratio to obtain a low melting point eutectic salt. Specifically, a phase diagram can be used to determine the ratio of lithium compounds to be mixed to obtain a mixed lithium source that can melt within the above temperature range.
[0077] Optionally, in order to further improve the exchange rate of lithium ions and sodium ions and make fewer sodium ions remain in the final product, the molar ratio of the lithium element in the lithium source to the sodium element in the P2 phase precursor with the coating layer is 1 to 20:1 (for example, 1:1, 5:1, 10:1 or 20:1).
[0078] S4. Post-processing
[0079] In order to further improve the performance of the prepared lithium cobalt oxide composite positive electrode material with a coating layer, the sodium ions released after ion exchange and the remaining lithium source when the lithium source is used excessively in the previous step are removed to improve the purity of the lithium cobalt oxide composite positive electrode material with a coating layer.
[0080] Therefore, after the crude positive electrode material is prepared in the previous step, it is further washed and dried to obtain a lithium cobalt oxide composite positive electrode material with a coating layer of T2 phase and O2 phase on the surface. After washing and drying, the Li / Co ratio is 0.70 to 0.74:1 (for example, 0.7:1, 0.72:1 or 0.74:1).
[0081] Optionally, the drying temperature is 80-150° C. (eg, 80° C., 100° C., 120° C. or 150° C.), and the drying time is ≥12 h.
[0082] An embodiment of the present invention provides a positive electrode, the active component of which includes the lithium cobalt oxide composite positive electrode material with a coating layer provided by the embodiment of the present invention, or the positive electrode material prepared by the preparation method provided by the embodiment of the present invention.
[0083] The battery provided by the embodiment of the present invention includes the positive electrode provided by the embodiment of the present invention.
[0084] Example 1
[0085] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor with a particle size of 6 to 8 μm and a D50 of 7 μm: Na 0.72 Co 0.98 Al 0.02 O2;
[0086] (2) P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2 and Al2O3 are uniformly mixed in a mass ratio of 100:0.3 and then sintered at high temperature. The sintering process is to increase the temperature to 650°C at 4°C / min, keep the temperature for 6 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor with a coating layer.
[0087] (3) The P2Na precursor with a coating layer and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein the molar ratio of lithium nitrate to lithium chloride is 71:29, and then molten salt ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain an Al2O3 coating layer with a main body of Li 0.72 Na 0.001 Co 0.98 Al 0.02 The T2 and O2 composite phase of the composite lithium cobalt oxide material has a particle size range of 6 to 8 μm, a D50 of 7 μm, and a coating layer thickness of 0.2 μm. The molar proportion of the O2 phase in the T2 and O2 composite phase is measured to be about 6%.
[0088] Example 2
[0089] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor with a particle size of 6 to 8 μm and a D50 of 7 μm: Na 0.72 Co 0.98 Al 0.02 O2;
[0090] (2) P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2 and Y2O3 were uniformly mixed in a mass ratio of 100:0.3 and then sintered at high temperature. The sintering process was to increase the temperature to 650°C at 4°C / min, keep the temperature for 6 hours, cool with the furnace, grind and sieve to obtain a surface-coated P2Na precursor.
[0091] (3) The P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2, lithium nitrate and lithium chloride were uniformly mixed in a Li / Na molar ratio of 10:1, and the molar ratio of lithium nitrate to lithium chloride was 71:29. Then, molten salt ion exchange was carried out. The ion exchange conditions were heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing and drying, and obtaining a Y2O3 coating layer with Li as the main body. 0.72 Na 0.001 Co 0.98 Al 0.02 The T2 and O2 composite phase of the composite lithium cobalt oxide material has a particle size range of 6 to 8 μm, a D50 of 7 μm, and a coating layer thickness of 0.2 μm. The molar proportion of the O2 phase in the T2 and O2 composite phase is measured to be about 7%.
[0092] Example 3
[0093] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor Na with a particle size of 6 to 8 μm and a D50 of 7 μm. 0.72 Co 0.98 Al 0.02 O2;
[0094] (2) P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2 and La2O3 were mixed in a mass ratio of 100:0.3 and then sintered at high temperature. The sintering process was to increase the temperature to 650°C at 4°C / min, keep the temperature for 6 hours, cool with the furnace, grind and sieve to obtain a surface-coated P2Na precursor.
[0095] (3) The P2Na precursor with a coating layer and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein the molar ratio of lithium nitrate to lithium chloride is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing and drying, and obtaining a La2O3 coating layer with Li 0.72 Na0.001 Co 0.98 Al 0.02 O2 T2 and O2 composite phase composite lithium cobalt oxide material Li 0.72 Na 0.001 Co 0.98 Al 0.02 O2, its particle size range is 6-8μm, D50 is 7μm, and the coating thickness is 0.2μm. The molar proportion of O2 phase in the T2 and O2 composite phase is about 6.5%.
[0096] Example 4
[0097] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor Na with a particle size of 6 to 8 μm and a D50 of 7 μm. 0.72 Co 0.98 Al 0.02 O2;
[0098] (2) P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2 and Nb2O5 were uniformly mixed in a mass ratio of 100:0.3 and then sintered at high temperature. The sintering process was to increase the temperature to 650°C at 4°C / min, keep the temperature for 6 hours, cool with the furnace, grind and sieve to obtain a surface-coated P2Na precursor.
[0099] (3) The P2Na precursor with a coating layer and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 10:1, wherein the molar ratio of lithium nitrate to lithium chloride is 71:29, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing and drying, and obtaining a Nb2O5 coating layer with Li as the main body. 0.72 Na 0.001 Co 0.98 Al 0.02 The T2 and O2 composite phase of the composite lithium cobalt oxide material has a particle size range of 6 to 8 μm, a D50 of 7 μm, and a coating layer thickness of 0.2 μm. The molar proportion of the O2 phase in the T2 and O2 composite phase is measured to be about 7%.
[0100] Example 5
[0101] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 700°C at 10°C / min, keep the temperature for 24 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor Na with a particle size of 6 to 8 μm and a D50 of 7 μm. 0.70 Co0.95 Al 0.05 O2;
[0102] (2) P2Na precursor Na 0.70 Co 0.95 Al 0.05 O2 and Nb2O5 were uniformly mixed in a mass ratio of 100:0.5 and then sintered at high temperature. The sintering process was to increase the temperature to 600°C at 10°C / min, keep the temperature for 12 hours, cool with the furnace, grind and sieve to obtain a surface-coated P2Na precursor.
[0103] (3) The P2Na precursor with the coating layer is uniformly mixed with lithium nitrate and lithium hydroxide at a Li / Na molar ratio of 2:1, wherein the molar ratio of lithium nitrate to lithium hydroxide is 62:38, and then ion exchange is performed. The ion exchange conditions are heating to 200°C at 1°C / min, keeping the temperature for 0.5h, cooling with the furnace, washing and drying, and obtaining a Nb2O5 coating layer with the main body of Li 0.70 Na 0.001 Co 0.95 Al 0.05 The T2 and O2 composite phase of the composite lithium cobalt oxide material has a particle size range of 6 to 8 μm, a D50 of 7 μm, and a coating layer thickness of 0.3 μm. The molar proportion of the O2 phase in the T2 and O2 composite phase is measured to be approximately 8%.
[0104] Example 6
[0105] (1) Na2CO3 and Co3O4 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 900°C at 1°C / min, keep the temperature for 8 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor Na with a particle size of 6 to 8 μm and a D50 of 7 μm. 0.74 CoO2;
[0106] (2) P2Na precursor Na 0.74 CoO2 and La2O3 were uniformly mixed in a mass ratio of 100:0.1 and then sintered at high temperature. The sintering process was to increase the temperature to 750℃ at 10℃ / min, keep the temperature for 6h, cool with the furnace, grind and sieve to obtain the surface-coated P2Na precursor Na 0.74 CoO2;
[0107] (3) The P2Na precursor with a coating layer and lithium chloride and lithium hydroxide are uniformly mixed at a Li / Na molar ratio of 20:1, wherein the molar ratio of lithium chloride to lithium hydroxide is 63:37, and then ion exchange is performed. The ion exchange conditions are heating to 300°C at 10°C / min, keeping the temperature for 0.5h, cooling with the furnace, washing and drying, and obtaining a La2O3 coating layer with the main body being Li 0.74 Na 0.001The T2 and O2 composite phase of CoO2 is a composite lithium cobalt oxide material, the particle size range is 6 to 8 μm, D50 is 7 μm, and the coating thickness is 0.1 μm. The molar proportion of the O2 phase in the T2 and O2 composite phase is about 5%.
[0108] Comparative Example 1
[0109] Li2CO3 and Co3O4 were uniformly mixed at a Li / Co molar ratio of 1.05 and then sintered at high temperature. The sintering procedure was to heat the temperature to 750°C at 4°C / min, keep it warm for 3.5 hours, then heat the temperature to 1000°C at 2°C / min, keep it warm for 6.5 hours, cool it with the furnace, grind and sieve it to obtain O3 phase lithium cobalt oxide positive electrode material with a particle size range of 6 to 8μm and D50 of 7μm.
[0110] Comparative Example 2
[0111] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain a P2Na precursor Na with a particle size of 6 to 8 μm and a D50 of 7 μm. 0.72 Co 0.98 Al 0.02 O2;
[0112] (2) P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2, lithium nitrate and lithium chloride were uniformly mixed in a Li / Na molar ratio of 10:1, wherein the molar ratio of lithium nitrate and lithium chloride was 71:29, and then molten salt ion exchange was carried out. The ion exchange conditions were heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing and drying, and obtaining T2 and O2 composite phase composite lithium cobalt oxide material Li 0.72 Na 0.001 Co 0.98 Al 0.02 O2.
[0113] Comparative Example 3
[0114] (1) Na2CO3, Co3O4 and Al2O3 were uniformly mixed in a stoichiometric ratio and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 4°C / min, keep the temperature for 16 hours, cool with the furnace, grind and sieve to obtain the P2Na precursor Na 0.72 Co 0.98 Al 0.02 O2;
[0115] (2) P2Na precursor Na 0.72 Co 0.98 Al 0.02O2, lithium nitrate and lithium chloride were uniformly mixed in a Li / Na molar ratio of 10:1, wherein the molar ratio of lithium nitrate and lithium chloride was 71:29, and then molten salt ion exchange was carried out. The ion exchange conditions were heating to 230°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing and drying, and obtaining T2 and O2 composite phase composite lithium cobalt oxide material Li 0.72 Na 0.001 Co 0.98 Al 0.02 O2;
[0116] (3) The T2 and O2 composite phase composite lithium cobalt oxide material and Al2O3 are uniformly mixed in a mass ratio of 100:0.3 and then sintered at high temperature. The sintering process is to increase the temperature to 650°C at 4°C / min, keep the temperature for 6 hours, cool with the furnace, grind and sieve to obtain a lithium cobalt oxide positive electrode material with a coating layer.
[0117] Experimental Example 1
[0118] (1) Photograph the XRD patterns of the finished positive electrode materials obtained in Example 1 and Comparative Example 3. Figure 1 and Figure 2 shown.
[0119] from Figure 1 It can be seen that the main peak of the finished cathode material obtained in Example 1 is located at 17.80±0.15°, and there is an O2 phase characteristic peak at 18.40±0.15°.
[0120] from Figure 2 It can be seen that the main peak of the positive electrode material prepared in Comparative Example 3 is located at 19.00±0.15°, and there is no O2 phase, which means that in Comparative Example 3, the T2 and O2 composite phase composite lithium cobalt oxide material is first prepared and then coated. Due to the high temperature of coating sintering, the O2 phase is transformed into the O3 phase.
[0121] (2) The CP-EPMA image of the P2Na precursor with coating layer obtained in the preparation process of Example 1 is as follows: Figure 3 As shown; the Al2O3 coating layer obtained in Example 1 is mainly Li 0.72 Na 0.001 Co 0.98 Al 0.02 The CP-EPMA diagram of O2 T2 and O2 composite phase composite lithium cobalt oxide material, such as Figure 4 shown.
[0122] from Figure 3 It can be seen that after the second sintering coating, a complete and uniform coating layer can be formed on the surface of the precursor;
[0123] from Figure 4 It can be seen that after ion exchange, the coating layer on the surface of T2 and O2 composite phase lithium cobalt oxide still exists stably.
[0124] Experimental Example 2
[0125] The positive electrode material prepared in the embodiment and comparative example is used as the positive electrode active material, Super P is a conductive agent, polyvinylidene fluoride (PVDF) is a binder, and the mass ratio of the above three is 90:5:5. An appropriate amount of N-methylpyrrolidone (NMP) is added to control the solid content of the slurry to 40%. The slurry is evenly mixed and coated on an aluminum foil current collector. After vacuum drying, it is taken out and hot pressed, and cut into a positive electrode sheet with a diameter of 12mm and a thickness of about 60μm. The button-type lithium-ion battery is assembled from the above-mentioned positive electrode sheet, lithium sheet negative electrode, separator between the positive and negative electrodes, and electrolyte. The assembled battery is placed in a 45°C high and low temperature box, and a constant current charge and discharge cycle test is carried out on the Xinwei battery test channel. The test conditions are: charge and discharge cut-off voltage 3.0-4.65V (vs Li + / Li), the first cycle charge and discharge rate was 0.1C, the second cycle charge and discharge rate was 0.2C, and the cycle was 50 cycles. The test results are shown in Table 1.
[0126] Table 1 Comparison of electrochemical performance of various examples and comparative examples
[0127]
[0128] It can be seen from Table 1 that the lithium cobalt oxide composite positive electrode materials with coating layers prepared in various embodiments of the present invention all have better electrochemical properties.
[0129] Comparing Example 1 with Comparative Example 1, the O3 phase lithium cobalt oxide prepared in Example 1 has higher first discharge capacity, higher first efficiency, higher initial capacity and capacity retention rate than those prepared in Comparative Example 1;
[0130] Comparing Example 1 with Comparative Example 2, the uncoated T2 and O2 composite phase lithium cobalt oxide positive electrode material in Example 1 has higher first efficiency and capacity retention rate than that in Comparative Example 2;
[0131] Comparing Example 1 with Comparative Example 3, the coated O3 phase lithium cobalt oxide positive electrode material in Example 1 has a higher first discharge capacity, a higher first efficiency, a higher initial capacity and a capacity retention rate than those in Comparative Example 3.
[0132] In summary, the lithium cobalt oxide composite positive electrode material with a coating layer provided by the present invention is mainly composed of lithium cobalt oxide in T2 phase and O2 phase. The capacity, rate and cyclability of lithium cobalt oxide in T2 phase are better than those in O3 phase. The lithium cobalt oxide in O2 phase can still maintain the stability of the crystal structure in a higher delithiation state than that in O3 phase. The lithium cobalt oxide in O2 phase undergoes a reversible phase change during the cycle and will not be converted into the thermodynamically stable lithium cobalt oxide in O3 phase or spinel phase. The metal oxide coating layer coated on the surface of the main body can suppress the interfacial side reaction problem of lithium cobalt oxide at high voltage, thereby further improving the electrochemical performance of the lithium cobalt oxide material. Therefore, the lithium cobalt oxide composite positive electrode material with a coating layer provided by the present invention has better electrochemical performance.
[0133] The preparation method provided by the present invention can achieve the coating of T2 and O2 composite phase lithium cobalt oxide materials by coating the P2Na precursor, thereby obtaining a composite positive electrode material having a surface coating layer and a main body of T2 and O2 composite phase lithium cobalt oxide. After sintering, the coating material generates a stable coating layer on the surface of P2Na, and the coating layer does not fall off after ion exchange, and a stable interface is generated on the surface of the positive electrode material. Under the premise of not affecting the diffusion of lithium ions, the interface side reaction is suppressed, the structure is stabilized, and the cycle stability of the material is improved; the preparation method is simple and easy, and the coating raw materials are easily available on the market, and can be used for industrial large-scale production. In addition, compared with the high-speed fusion coating or low-temperature sintering coating of the finished O2 phase lithium cobalt oxide material, this coating method is a coating layer formed at high temperature, so the bonding of the coating layer is significantly higher.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium cobalt oxide composite positive electrode material with a coating layer, characterized in that: include: A main body and a coating layer coated outside the main body, wherein the chemical formula of the main body is Li x Na y Co 1-z M z O2, wherein 0.7≤x≤0.74, 0<y≤0.1, 0≤z≤0.1, and M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn and Nb; The coating layer is a metal oxide, and the thickness of the coating layer is less than or equal to 1 μm; The crystalline phase in the main body is a composite phase of T2 and O2.
2. The lithium cobalt oxide composite positive electrode material with a coating layer according to claim 1, characterized in that: The invention comprises at least one of the following technical features (1) to (5): (1) The thickness of the coating layer is 0.05 to 1 μm; (2) The particle size of the lithium cobalt oxide composite positive electrode material with a coating layer is 1 to 20 μm; (3) The main peak of the XRD spectrum of the lithium cobalt oxide composite positive electrode material with a coating layer is located at 17.80±0.15°, and there is an O2 phase characteristic peak at 18.40±0.15°; (4) The metal oxide is at least one selected from aluminum oxide, magnesium oxide, yttrium oxide, niobium oxide, lanthanum oxide and zirconium oxide; (5) The amount of O2 phase material in the T2 and O2 composite phase is greater than 0 and less than or equal to 10%.
3. A method for preparing a lithium cobalt oxide composite positive electrode material with a coating layer as claimed in claim 1 or 2, characterized in that: include: The sodium cobaltate P2 phase precursor is mixed with a coating material and then subjected to coating solid phase sintering, wherein the coating material is the metal oxide and the sintering temperature is 550-750° C., to obtain a P2 phase precursor with a coating layer; The P2 phase precursor with the coating layer is mixed with a lithium source and then subjected to molten salt ion exchange, so that the lithium element is exchanged with the sodium element in the P2 phase precursor with the coating layer, so that the P2 phase is transformed into a T2 and O2 composite phase.
4. The preparation method according to claim 3, characterized in that: Before the coating solid phase sintering is performed, the method further includes obtaining the sodium cobaltate P2 phase precursor: Synthesize solid-phase sintering of a first mixed material, wherein the first mixed material includes sodium and cobalt elements, wherein the molar ratio of the sodium element to the cobalt element is 0.6 to 1.0:1, to obtain a sodium cobaltate P2 phase precursor; Optionally, the first mixture further includes an M element, and the M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn and Nb.
5. The preparation method according to claim 4, characterized in that: The cobalt element in the first mixed material is provided by a cobalt source, and the cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide; Optionally, the M element is doped in the cobalt source; Optionally, the sodium element in the first mixed material is provided by a sodium source, and the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
6. The preparation method according to claim 4, characterized in that: The sintering conditions of synthetic solid phase sintering are: heating to 700-900°C at 1-10°C / min and keeping the temperature for 8-30h.
7. The preparation method according to claim 3, characterized in that: The invention comprises at least one of the following technical features (1) to (4); (1) The sintering conditions of the coated solid phase sintering are: heating to 550-750°C at 1-10°C / min and keeping warm for 3-12h; (2) The conditions for molten salt ion exchange are: heating to 180-300°C at 1-10°C / min and keeping warm for 0.5-12h; (3) The lithium source is composed of at least two of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide, which can be eutectic in the range of 180 to 300° C.; (4) The molar ratio of the lithium element in the lithium source to the sodium element in the P2 phase precursor with the coating layer is 1 to 20:
1.
8. The preparation method according to claim 3, characterized in that: After the molten salt ion exchange, a crude positive electrode material is obtained. After the crude positive electrode material is obtained, it is further washed and dried to obtain a lithium cobalt oxide composite positive electrode material with a coating layer on the surface; Optionally, the drying temperature is 80-150° C., and the drying time is ≥12 h.
9. A positive electrode, characterized in that The active component thereof comprises the lithium cobalt oxide composite positive electrode material with a coating layer as claimed in claim 1 or 2, or the positive electrode material prepared by the preparation method as claimed in any one of claims 3 to 8.
10. A battery, characterized in that: Comprising the positive electrode as claimed in claim 9.
Citation Information
Cited By
Composite-phase core-shell lithium cobalt oxide as well as preparation method and application thereof
CN121054649A
Composite lithium cobalt oxide positive electrode material, preparation method thereof and lithium ion battery
CN121076074A
O2-phase lithium cobalt oxide positive electrode material and preparation method and application thereof
CN121134846A
Positive electrode material, secondary battery, and electronic device
WO2026193690A1